PHYTOREMEDIATION PLANNING IN THE CASE OF FORMER INDUSTRIAL SITES - BOROŞ, Melania-Nicoleta; MICLE, Valer; FLĂMÎND, Lazăr; SUR, Ioana Monica (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
Contaminated soils from former industrial sites need urgent measures of treatment in order to be used for other purposes. Because of the large spaces that industrial sites usually occupy, green technologies have to be chosen to treat the soil while protecting the environment. Phytoremediation is an environmentally friendly technology that uses plants to decontaminate soils. The main advantage is the low cost compared to other techniques and the main disadvantage is the time factor because phytoremediation requires long period of time to treat the polluted soil. This paper presents specific features that must be taken into consideration when planning and implementing phytoremediation projects. Pollutants concentration and soil properties limit the application of phytoremediation. A clean-up plan is prepared taking into consideration limiting factors and then the remediation measures are implemented. The project needs long-term monitoring to determine the quantity of contaminants in soils during its implementation. The main purpose is to provide a safe environment for humans’ health while improving the ecological situation of the former industrial sites.